Progress towards the development and implementation of an unambiguous copper wire fingerprinting system - Poole, Martin (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2003)
The Telecommunications industry in Southern Africa is faced with the problem of theft of the signal carrying copper wire, both from the ground and from telephone poles. In many cases, if the offenders are caught, the prosecuting party has no way of proving that the wire is the property of any one Telecommunication company, as any inked markings on the insulating sheaths have been burned off along with the insulation and protective coatings themselves. Through this work we * describe the problem, * specify the necessary and preferred technical properties of a viable solution, * report the preliminary investigations into the devising of an unambiguous "fingerprinting" of the 0.5 mm wires, including some of those solutions that, upon investigation, appear non-viable, * describe the development and implementation of an electrochemical marker with detection mechanism which has shown in proof-of-principle to work, * outline the road-map of necessary future work.
Keywords: Electroplating; Copper; Telecommunication; Theft -- Prevention